Structure-based drug design of 1, 3, 5-triazine and pyrimidine derivatives as novel FGFR3 inhibitors with high selectivity over VEGFR2. Issue 10 (15th May 2020) - Kuriwaki, Ikumi; Kameda, Minoru; Hisamichi, Hiroyuki; Kikuchi, Shigetoshi; Iikubo, Kazuhiko; Kawamoto, Yuichiro; Moritomo, Hiroyuki; Kondoh, Yutaka; Amano, Yasushi; Tateishi, Yukihiro; Echizen, Yuka; Iwai, Yoshinori; et al.
Graphical abstract: Abstract: Fibroblast growth factor receptor 3 (FGFR3) is an attractive therapeutic target for the treatment of bladder cancer. We identified 1, 3, 5-triazine derivative 18b and pyrimidine derivative 40a as novel structures with potent and highly selective FGFR3 inhibitory activity over vascular endothelial growth factor receptor 2 (VEGFR2) using a structure-based drug design (SBDD) approach. X-ray crystal structure analysis suggests that interactions between 18b and amino acid residues located in the solvent region (Lys476 and Met488), and between 40a and Met529 located in the back pocket of FGFR3 may underlie the potent FGFR3 inhibitory activity and high kinase selectivity over VEGFR2.